2014
DOI: 10.3390/ijerph110100773
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sedentary Behavior, Motivation, Barriers and Strategies to Reduce Sitting Time in Older Women: A Qualitative Investigation

Abstract: Sedentary behavior defined as time spent non-exercising seated or reclining posture has been identified has a health risk and associated with frailty and disablement for older adults. Older adults are the most sedentary segment of society. To date no study has investigated the determinants of sedentary behavior in older adults. This study reports a qualitative investigation of the determinants of sedentary behavior, strategies and motivator to reduce sitting time by structured interviews in a group of communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
182
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(209 citation statements)
references
References 38 publications
18
182
1
3
Order By: Relevance
“…Scheduling SE was categorized into three psychological subcategories (productivity, focused, tired) and two situational subcategories (studying, screen time leisure; Chastin, Fitzpatrick, Andrews, & DiCroce, 2014;Greenwood-Hickman, Renz, & Rosenberg, 2015). Each subcategory was measured by three items, totaling to nine psychological items and six situational items.…”
Section: Threat Termmentioning
confidence: 99%
“…Scheduling SE was categorized into three psychological subcategories (productivity, focused, tired) and two situational subcategories (studying, screen time leisure; Chastin, Fitzpatrick, Andrews, & DiCroce, 2014;Greenwood-Hickman, Renz, & Rosenberg, 2015). Each subcategory was measured by three items, totaling to nine psychological items and six situational items.…”
Section: Threat Termmentioning
confidence: 99%
“…Research indicates that among this group time spent sedentary is independently related to functional fitness (Santos et al, 2012), while individuals with lower levels of SB appear more likely to age successfully (Balboa-Castillo, Leon-Munoz, Graciani, Rodriguez-Artalejo, & Guallar-Castillon, 2011;Dogra & Stathokostas, 2012). Of concern to this paper, although relatively few studies have investigated SB in the older population (Chastin, Fitzpatrick, Andrews, & DiCroce, 2014), one might expect much of this behaviour to occur at home where this group can spend extended periods . In a population-based random sample (n ¼ 11 918), Brasche and Bischof (2005) found that individuals aged 65 years and over (n ¼ 2467) spent, on average, 19.5 hours per day at home (more time than any other age group).…”
Section: Introductionmentioning
confidence: 89%
“…Comparatively few studies have investigated the potential environmental correlates of PA and SB in older adults (Chastin et al, 2014;Van Cauwenberg et al, 2011). Equally relevant to the research reported here, few have explored such associations in stroke survivors (English, Manns, Tucak, & Bernhardt, 2014) or people with dementia (Stubbs et al, 2014).…”
Section: The Environmental Correlates Of Pa and Sb In Older Adultsmentioning
confidence: 95%
See 2 more Smart Citations